A New Route to Azafluoranthene Natural Products via Direct Arylation - Ponnala, Shashikanth (2013)
Microwave-assisted direct arylation was successfully employed in the synthesis of azafluoranthene alkaloids for the first time. Direct arylation reactions on a diverse set of phenyltetrahydroisoquinolines produces the indeno[1,2,3-ij]isoquinoline nucleus en route to a high yielding azafluoranthene synthesis. The method was used as a key step in the efficient preparation of the natural products rufescine and triclisine. As demonstrated herein, this synthetic approach should be generally applicable to the preparation of natural and un-natural azafluoranthene alkaloids as well as “azafluoranthene-like” isoquinoline alkaloids.